Contributions of epsinR and gadkin to clathrin-mediated intracellular trafficking - Hirst, Jennifer (Mol Biol Cell, 2015)
The precise functions of most of the proteins that participate in clathrin-mediated intracellular trafficking are unknown. We investigated two such proteins, epsinR and gadkin, using the knocksideways method, which rapidly depletes proteins from the available pool by trapping them onto mitochondria. Although epsinR is known to be an N-ethylmaleimide–sensitive factor attachment protein receptor (SNARE)-specific adaptor, the epsinR knocksideways blocked the production of the entire population of intracellular clathrin-coated vesicles (CCVs), suggesting a more global function. Using the epsinR knocksideways data, we were able to estimate the copy number of all major intracellular CCV proteins. Both sides of the vesicle are densely covered, indicating that CCVs sort their cargo by molecular crowding. Trapping of gadkin onto mitochondria also blocked the production of intracellular CCVs but by a different mechanism: vesicles became cross-linked to mitochondria and pulled out toward the cell periphery. Both phenotypes provide new insights into the regulation of intracellular CCV formation, which could not have been found using more conventional approaches.